2018
DOI: 10.3390/molecules23082027
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Purification of Galloyl, Caffeoyl, and Hexahydroxydiphenoyl Esters of Glucoses from Balanophora simaoensis by High-Speed Countercurrent Chromatography and Their Antioxidant Activities In Vitro

Abstract: High-speed counter-current chromatography was used to separate and purify galloyl, caffeoyl, and hexahydroxydiphenoyl esters of glucoses from the aerial parts of the parasitic plant Balanophora simaoensis for the first time using n-hexane-ethyl acetate-methanol-water (1:2:1:2, v/v) as the optimum solvent system. Accordingly, 1-O-(E)-caffeoyl-3-O-galloyl-β-d-glucopyranose (I, 12.5 mg), 1-O-(E)-caffeoyl-3-O-galloyl-4,6-(S)-hexahydroxydiphenoyl-β-d-glucopyranose (II, 27.2 mg), and 1-O-(E)-caffeoyl-4,6-(S)-hexahyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…17 It has been demonstrated that the chemical components of Balanophora polyandra Griff include phenylpropanoids, flavonoids, tannins and polysaccharides etc, which have medicinal functions, such as anti-inflammation, liver protection, anti-oxidation and anti-cancer as well as other biological effects. 18 More recently, we found that Balanophora polyandra Griff polysaccharides (BPPs) significantly inhibited the proliferation of ovarian cancer cells via P53mediated pathway. 19 However, to date, there have been no reports about the influence of BPPs on renal fibrosis and the underlying mechanisms.…”
Section: Balanophora Polyandra Griff Belonging To the Familymentioning
confidence: 99%
See 1 more Smart Citation
“…17 It has been demonstrated that the chemical components of Balanophora polyandra Griff include phenylpropanoids, flavonoids, tannins and polysaccharides etc, which have medicinal functions, such as anti-inflammation, liver protection, anti-oxidation and anti-cancer as well as other biological effects. 18 More recently, we found that Balanophora polyandra Griff polysaccharides (BPPs) significantly inhibited the proliferation of ovarian cancer cells via P53mediated pathway. 19 However, to date, there have been no reports about the influence of BPPs on renal fibrosis and the underlying mechanisms.…”
Section: Balanophora Polyandra Griff Belonging To the Familymentioning
confidence: 99%
“…Balanophora polyandra Griff , belonging to the family Balanophoraceae , is a natural medicinal mushroom living in association with the root system of many different host plants, especially the evergreen shrubs in Hubei, Hunan and Yunnan provinces in China 17 . It has been demonstrated that the chemical components of Balanophora polyandra Griff include phenylpropanoids, flavonoids, tannins and polysaccharides etc, which have medicinal functions, such as anti‐inflammation, liver protection, anti‐oxidation and anti‐cancer as well as other biological effects 18 . More recently, we found that Balanophora polyandra Griff polysaccharides (BPPs) significantly inhibited the proliferation of ovarian cancer cells via P53‐mediated pathway 19 .…”
Section: Introductionmentioning
confidence: 95%
“…Anti-inflammatory activity of EBF was evaluated by an experimental model of gouty arthritis as previously described by Faires and McCarty. 6 Monosodium urate crystals were synthesized using the procedure described by Faires and McCarty. 6 The crystals were suspended in 9% sterile saline (48 mg/mL) prior to use.…”
Section: Urate-induced Synovitismentioning
confidence: 99%
“…6 Monosodium urate crystals were synthesized using the procedure described by Faires and McCarty. 6 The crystals were suspended in 9% sterile saline (48 mg/mL) prior to use. Similar to the carrageenan model, each group was administered the ethanol extract EBF (350, 500 mg/kg p.o), diclofenac (20 mg/kg), and negative control (Na-CMC 0,5%) once a day for 5 consecutive days.…”
Section: Urate-induced Synovitismentioning
confidence: 99%
See 1 more Smart Citation